THE IMPORTANCE OF TEACHING THE MODELING DEPARTMENT OF COMPUTER SCIENCE FOR MIDDLE SCHOOL STUDENTS - Tileubai С.Ш.; Toleu Н.С.; Kazbekova Г.Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Today, the rapid development of information and communication technologies leads to radical changes in the field of cognitive activity, in particular in education. An important change is the method of modeling used in the didactic practice of computer science. Modeling is one of the most common methods of studying processes and phenomena, which is widely used in research and teaching. The article analyzes the role of modeling as a universal method of studying complex objects in the teaching of computer science, and shows ways to develop the importance of modeling as a basis for teaching in general software. The role of the model in teaching computer science to high school students focuses on the importance of teaching in the modeling of computer science, and ways to increase students’ interest and skills in considering the technology of teaching methods.